2018
DOI: 10.3389/fphys.2018.00461
|View full text |Cite
|
Sign up to set email alerts
|

Stress Profile in Remotely Piloted Aircraft Crewmembers During 2 h Operating Mission

Abstract: Emotional stability plays a key role in individual and team performance during both routine activities and management of unexpected emergencies. Using a psycho-physiological approach, the stress response was investigated in drone operators in service.Methods: Salivary α-amylase (sAA), galvanic skin response (GSR) and anxiety were assessed over a 2-h operating flight.Results: Compared to baseline values, GSR and sAA values increased in operating conditions. Moreover, these values were higher in Pilots than in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Compared to baseline values, EDA and sAA values increased in operating conditions and were also associated with an increase in anxiety level. The authors suggest that this is likely related to increased arousal and perceived self-control, and might facilitate an increase in performance and self-confidence [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to baseline values, EDA and sAA values increased in operating conditions and were also associated with an increase in anxiety level. The authors suggest that this is likely related to increased arousal and perceived self-control, and might facilitate an increase in performance and self-confidence [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it has been found that 14 to 16% of the UAV operators in the US military reported high levels of mental fatigue during missions (Wayne et al 2014;Werner et al 2020). Further existing research shows very little empirical experiments in this field, despite demonstrations of increased emotional distress among drone remote UAV pilots (Valenzano et al 2018). While there may be some overlaps of interest, more generally the context in which remote crew and UAV pilots operate differ in operation, outcome, and duration.…”
Section: The Handover Between Manual and Automationmentioning
confidence: 99%